Small bowel resistances and the gastroduodenal brake. Issue 8 (August 1987) - Parr, N J; Grime, J S; Baxter, J N; Critchley, M; Mackie, C R
Abstract : Osmoreceptors in the upper small bowel may delay gastric emptying by inhibiting fundal tone and/or by increasing outflow resistances. In this study we examined the contribution of postpyloric resistances to this braking system. Seven dogs had gastric emptying of 250 ml 15% dextrose, labelled with 99mTc-DTPA, measured by gamma camera imaging (preoperative studies: n = 21). A proximal duodenal cannula was inserted and studies repeated in four modes: with the cannula closed (n = 14); with total diversion of gastric effluent through the cannula (n = 7); with diversion and downstream reinstillation of effluent at a constant rate (n = 14) equivalent to emptying calculated from studies without diversion; and with diversion and total reinstillation of effluent (n = 14). Gastric emptying at 90 minutes was similar in preoperative studies (48 +/- 5% - mean +/- SEM) and in those with the cannula closed (50 +/- 3%). By comparison 'total diversion' produced rapid emptying over 90 minutes (97 +/- 1%; p less than 0.001). Reinstillation of effluent at a constant rate reduced the 90 minute emptying to 59 +/- 6%, and total reinstillation slowed emptying further to 37 +/- 4% (p less than 0.05). Neither reinstillation protocol yielded gastric emptying rates that were significantly different from those in studies without diversion. With total reinstillation, emptying and hence reinstillation rates were more variable, proceeding in a step and plateau fashion. We conclude that canine jejunal osmoreceptor activity is mediated through the stomach, with postpyloric resistances playing little or no role. Gastric emptying curve analysis suggested that increments of rapid small bowel filling provoke exaggerated braking responses.